Visual loss with chronic meningeal and systemic inflammation. Issue 1 (13th August 2021) - Fernandes, Peter M; Kinton, Lucy; Madill, Stephen; Burgess, Frederick R; McRorie, Euan; Dhaun, Neeraj; Kidd, Desmond; Lachmann, Helen J; Davenport, Richard J; Hunt, David
Abstract : A 46-year-old man presented with worsening vision in the context of long-standing optic disc changes, bilateral sensorineural hearing loss, chronic aseptic meningitis, rash, arthralgia and raised inflammatory markers. The differential diagnoses of neoplasia, infection and inflammation are discussed. We highlight a condition that can present to adult neurologists, with successful diagnosis leading to targeted treatments that transform patient outcomes. This case was presented at the Association of British Neurologists Annual Meeting 2020 as a Clinicopathological Conference (CPC).